The formation of centres of excellence in subsidiaries of first tiers in brazil: an analysis of the organizational knowledge perspective - Wilian Gatti Junior; Ana Paula Franco Paes Leme Barbosa (Internext: Revista Eletrônica de Negócios Internacionais, 2013)
In Brazil, the flex fuel vehicle headlined a change in the role of subsidiaries that not only developed the new technology, as they became centres of excellence for applications involving alternative fuels. Many researches have studied the mechanisms that lead to the establishment of these centres in emerging countries, focusing on the role of the matrix or in the conditions of the countries that host the subsidiary. This article will identify the organizational knowledge creation that enabled subsidiaries to become centres of excellence. For this, we adopted an approach of multiple case studies with three pioneers in the development of this technology in Brazil: Bosch, Delphi and Magneti Marelli. The survey found that organizational knowledge was constructed from two sources (internal and external) with evidence in the way of knowledge conversion proposed in the SECI model: explicit knowledge, reported in company records, reports development, database, market inputs and the relationship with mothers and assemblers (externalization and combination), and tacit knowledge to the study of technical solutions ( internalization ) and the exchange of experiences between different generations of engineers ( socialization ).